Prevalence of Tritrichomonas foetus in beef bulls slaughtered at two abattoirs in northern Australia. Issue 5 (25th January 2022) - Irons, PC; McGowan, M; de Assis, PM; Randhawa, I; Awawdeh, L; Mugwabana, J; Barnes, TS; Boe‐Hansen, G; McCosker, K; Fordyce, G
Abstract : Bovine trichomoniasis, caused by the protozoal parasite Tritrichomonas foetus, is a highly contagious venereal disease characterised by early pregnancy loss, abortion and pyometra. Persistently infected bulls and cows are the primary reservoirs of infection in infected herds. This research investigated the prevalence of T. foetus infection in bulls from properties located across northern Australia and New South Wales. Preputial samples were collected from 606 bulls at slaughter and tested for T. foetus using the VetMAX‐Gold Trich Detection Kit (Thermo Fisher Scientific). The apparent prevalence of T. foetus infection varied between regions, with northern regions in the Northern Territory, Queensland and Western Australia showing a prevalence of 15.4%, 13.8% and 11.4%, respectively. There was some evidence of an association between infection and postcode (P = 0.06) and increasing bull age (P = 0.054). This study confirms that T. foetus infection is likely to be present in many beef breeding herds and contributing to lower than expected reproductive performance, particularly across northern Australia.